Sistem Informasi Booking Room Badan Pengusahaan Batam Menggunakan Metode Object Oriented Analysis and Design - Sabtu, Sabtu; Veza, Okta; Crystalia, Nike; Syofiawan, Doni; Adi, Novi Hendri (Universitas Lampung, 2023)
At the Batam Enterprise Agency in the Public Relations, Promotion, and Protocol Bureau section, when borrowing rooms they still use manual processes, and paper forms in the borrowing process, which results in less effective record keeping. So the author created a room lending dashboard information system. The aim of this research is to design a meeting room lending dashboard information system. The method used in this research is Object Oriented Analysis and Design (OOAD) which has stages of analysis, design, implementation, and experimentation, while system design uses Unified Modeling Language (UML) modeling, system flow diagrams consisting of (use case diagrams, activity diagrams, sequence diagram and class diagram), the result of this research is to produce a dashboard information system for borrowing meeting rooms which can make work easier and make room borrowing schedules well organized.Kata kunci: OOAD, Peminjaman Ruang, Sistem Informasi, Unified Modeling Language